2017
DOI: 10.5539/jel.v6n1p322
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Relationship between Organizational Stress and Employee Performance: A Research on Staff Working on Provincial Directorate of Youth and Sports

Abstract: The purpose of this research is to study the relation between the level of organizational stress at the staff of the Youth Services and Sports Provincial Directorate and their performance. The study group of research, Istanbul province in the Uskudar district officials operating in the Youth Services and Sports Provincial Directorate constitute a total of 96 staff, including 36 women and 60 men. In this research, "Job Strain Questionnaire Scale" that was developed firstly by Theorell et al. (1988) and adapted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…As stated in several studies, the effect of psychological pressure on human resource performance finds inconsistent results such as Duraku and Hoxha (2018) and Spivey, Havrda, Stallworth, Renfro and Chisholm-burns (2020), they report that psychological pressure has significant effect on performance. While in other studies, psychological stress is reported to have no significant effect on performance (Dendle et al, 2018;Goksel, Caz, Yazici & Ikizler, 2017). Substantially, psychological distress causes organizational members to lose focus, so they could not make optimal contributions, thus declining their performance (Ismail, Saudin, Ismail, Samah, Bakar & Aminudin, 2015;Khuong & Yen, 2016).…”
Section: Introductionmentioning
confidence: 96%
“…As stated in several studies, the effect of psychological pressure on human resource performance finds inconsistent results such as Duraku and Hoxha (2018) and Spivey, Havrda, Stallworth, Renfro and Chisholm-burns (2020), they report that psychological pressure has significant effect on performance. While in other studies, psychological stress is reported to have no significant effect on performance (Dendle et al, 2018;Goksel, Caz, Yazici & Ikizler, 2017). Substantially, psychological distress causes organizational members to lose focus, so they could not make optimal contributions, thus declining their performance (Ismail, Saudin, Ismail, Samah, Bakar & Aminudin, 2015;Khuong & Yen, 2016).…”
Section: Introductionmentioning
confidence: 96%
“…[9] Underline the significance of advancing a supportive workplace and sufficient supervision bolster, as these elements influence employees' work related performances and discernments. [10,11] 2 Theory: interpersonal emotional management theory and job satisfaction This work is inspired from social exchange theory. At the same time, study is important in terms of job satisfaction has which remained an intriguing point in the managerial consciousness research and supervision.…”
Section: Introductionmentioning
confidence: 99%
“…People spend most time for working during the day, so the work life is very important for employees (Bozyiğit and Durmuş, 2018). During the develop and change employees feel some stress (Göksel et al, 2017). And the stress sometimes causes negative behaviors.…”
Section: Introductionmentioning
confidence: 99%